Reasons for the decline in reading and writing skills among students in grades (3-8) from the perspective of Arabic language teachers in the South Sharqiyah Governorate (The International Journal of Educational Sciences and Arts, 2026)
This study aims to investigate the causes of low reading and writing proficiency among students in grades (3–8) from the perspective of Arabic language teachers in schools of the South Al Sharqiyah Governorate in the Sultanate of Oman. Reading and writing skills represent fundamental pillars of the educational process, as they constitute the basis of learning and serve as gateways to knowledge acquisition and critical thinking. The researchers adopted the descriptive analytical approach, using a questionnaire as the main data collection instrument administered to a sample of male and female Arabic language teachers.The findings revealed that the decline in reading and writing skills is attributed to multiple interrelated factors classified into five main domains. First, student-related factors, most notably neglecting reading and writing assignments (93%), fear and shyness of classroom participation (89%), and frequent absenteeism before completing the academic syllabus (65%). Second, classroom and instructional factors, including overcrowded classrooms (92%), dense and difficult curricular content (80%), and excessive focus on examinations at the expense of practical application (56%). Third, family-related factors, which were identified as the most influential, including limited parental follow-up (95%), weak family–school cooperation (94%), and parents’ lack of strategies to address their children’s learning difficulties (91%). Fourth, administrative and supervisory factors, such as limited reinforcement of students participating in language activities and competitions (63%), scarcity of specialized discussion forums addressing reading and writing difficulties (60%), and inadequate supervisory follow-up of remedial and enrichment plans (41%). Fifth, factors related to the educational system, particularly the promotion of low-achieving students without ensuring mastery of basic skills, a practice supported by 79% of the teachers, which was found to widen learning gaps and lead to cumulative learning deficiencies in subsequent grades.Based on these findings, the study recommends strengthening the educational role of the family through awareness and guidance programs that enhance school–community partnerships, activating remedial and enrichment plans under the supervision of school administrations and educational supervisors, reducing classroom density to allow for individualized follow-up and continuous assessment, reviewing curricula to align with students’ abilities and real-life contexts, and developing assessment methods to be formative and comprehensive while accounting for individual differences. Additionally, the study emphasizes training teachers on modern strategies for teaching Arabic and diagnosing reading and writing difficulties, and reconsidering promotion policies to ensure students’ mastery of essential skills prior to grade advancement.
Keywords: Decline; Level; Reading; Arabic Language; Teachers